Contrastive Analysis of English and Indonesian Idioms of Human Body - Cindy Adelina; Suprayogi Suprayogi (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2020)
This research analyzes English Idioms which are equivalent in Indonesian Idioms especially idioms inrelation to human body. This research is conducted due to limited research on contrastive analysis in bothlanguages in the field of semantics. The method used in this research is descriptive qualitative method. Thedata in this research are idioms in English which have an equivalent in Indonesian idioms and vice versataken from dictionary of idioms and websites discussing idioms in both languages. Data are analyzed underthe framework of idiom classification by Fernando (1996) and types of contrastive analysis by Lado (1957).Based on the analysis that has been done, it can be concluded that mostly the equivalence of English andIndonesian idioms are in the form of pure idioms. In the level of contrastive analysis, the idioms arecategorized into three. The first is idioms in Indonesian and English which have similar meanings andsimilar forms of expressions. The second is idioms in Indonesian and English which have different meaningsbut similar forms of expressions. The third is idioms in Indonesian and English which have similarmeanings but different forms of expressions. The causes of similarities between the two idioms betweenEnglish and Indonesian is cultural factors between English and Indonesian in terms of percieving human body.Keywords: contrastive analysis, English Idiom, Indonesian Idiom, human body.